Penerapan Progressive Muscle Relaxation untuk Menurunkan Kadar Gula Darah pada Penderita Diabetes Mellitus Tipe 2 - Anastasya Bella Natalia; Novita Elisabeth Daeli; Aniska Indah Fari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Type 2 diabetes mellitus (DM) is a chronic metabolic disease caused by insulin resistance, leading to increased blood sugar levels. DM can cause both acute and chronic complications. One non-pharmacological therapy that can help control blood sugar levels is progressive muscle relaxation (PMR). This technique involves tensing and relaxing certain muscles, allowing the hormone cortisol to work to stabilize blood sugar levels. The design used in this case study was a progressive muscle relaxation intervention for patients with Type 2 DM in the inpatient ward of Palembang Hospital, conducted once for three consecutive days with a duration of 15-20 minutes. Blood sugar levels were measured using a glucometer twice before and after the intervention. The results obtained from the three respondents over three days showed a decrease in blood sugar levels before and after the intervention. The application of progressive muscle relaxation has an effect on reducing blood sugar levels in patients with Type 2 DM.